Relationships between Breakthrough Curves and X-ray Computed Tomography Analyzed Macropore Characteristics - C. Hinz, A. Spangenberg, Y. Nagarajarao (Journal of the Indian Society of Soil Science, 2017)
Ten undisturbed soil monoliths of clayey Pelosol at Gottingen, Germany covering the horizons Ah and P were collected. Some columns were left at natural humidity, some were oven-dried to simulate drought situations in forest soils in consequence of climate change. In seven columns, four micro-lysimeters, each, were installed at half height in order to obtain data for analysis of single solute pathways. A fixed amount of KBr tracer was applied to the humus layer. The columns were irrigated with CaCl2. Column output and lysimeter output were collected and analyzed to record breakthrough curves. Bimodal analytical convection dispersion equation (CDE) solutions were fitted for the column outputs using a non-linear least square fit. A simple CDE solution did not fit well. This supports the model of two overlaying transport phenomena. After breakthrough recording was complete, all columns were scanned using X-ray computed tomography (CT). From the CT data 3-D reconstructions of the porous system were created for visual inspection, and the exact pathways for macropores along the micro-lysimeters were determined. Additionally, indices of the pore structure were computed to compare with the slow and fast dispersivity values from the bimodal CDE fit. The variation in micro-lysimeter performance could be explained using the 3-D reconstruction. Statistically significant differences between the pore structure of wet and dried columns after the end of irrigation could not be identified. The pore index has generally a negative linear relationship with the fast dispersivity, and a positive linear relationship with the slow dispersivity. These relations are stronger in topsoil. The CT pictures and 3-D re-constructions provide an interesting insight into the soil pore system and may help to understand man-made drought problems due to climate change.